The Existence of Marble and Onyx Handicrafts in Gamping Village in Improving Community’s Welfare - Mintarti W, Sri Umi; Soesilo, Y H; Putri, R D; Rachmawati, D; ., Annisya (KnE Social Sciences, 2018)
The business of marble and onyx stone crafts in Gamping village has established before Indonesia’s independence. In the Dutch colonial era, there are already handicrafts that make gravestone in which many are sent abroad. The existence of this business is still visible even though the crisis has hit the economy of Indonesia. This study was conducted to find out why this business can still exist and its impact on the welfare of the community. This research is a qualitative research conducted in Gamping village with marble and onyx stone crafts entrepreneur as the research subject. The sources of information are obtained from employers, community leaders, and housewives. Furthermore, the research instrument in this study was interview and documentation. The results showed that these entrepreneurs are highly motivated to try in the field of crafts as well as being honest and responsible in fulfilling the orders. Their willingness to be independent is very high even only with limited capital. However, this business is also experienced several ups and downs. In 1985-2005, this has experienced a glory while after 2005, this has encountered a decrease in the orders. The existence of this business is very helpful to meet the needs of life and to provide prosperity for the community in Gamping village. Therefore, this needs government intervention especially in product development and marketing so that this business can maintain its existence. Keywords: marble and onyx SMEs existence, motivation, honest and responsible, people’s prosperity.